(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
Feuerbach argued that God is not the creator of man, but man is the creator of God. It led him to the conclusion that the secret of theology is anthropology. According to Stirner, Feuerbach proposes, at most, formal reclassification of concepts, still being a religious thinker, because he deifies the species-understood Man. The article is devoted to Stirner’s criticism of Feuerbach and polemic with researchers who perceive Stirner as an amoralistic antihumanist.